Modes of Facilitator Skills for Group Learning Among Design and Technology Teachers in Secondary Schools - Mohamad, Norsuhaidah; Masek, Alias (Indonesian Journal of Teaching in Science, 2021)
The purpose of this study was to verify the constructs of facilitator skill for a group learning in Design and Technology subjects in secondary schools. The method used descriptive quantitative method. This study covers several tests such as content validity, construct validity, pilot studies and internal reliability test. Sample value that involved in this study was 273. The instrument is based on Heron’s Model (2006) which involves constructs and elements in facilitator skills. The results show that the high mode of facilitation is the hierarchical mode with mean value 4.32. Followed by cooperative (4.14) and autonomous mode (3.96). This is because the facilitator still determines the objectives, learning process, interprets and gives meaning, provide structure and take full responsibility for the decisions making in learning process.